2009
DOI: 10.1111/j.1467-9280.2009.02347.x
|View full text |Cite
|
Sign up to set email alerts
|

The Deliberation-Without-Attention Effect

Abstract: Proponents of unconscious-thought theory assert that letting the unconscious "mull it over" can enhance decisions. In a series of recent studies, researchers demonstrated that participants whose attention was focused on solving a complex problem (i.e., those using conscious thought) made poorer choices, decisions, and judgments than participants whose attention was distracted from the problem (i.e., those purportedly using unconscious thought). We argue that this finding, rather than establishing the existence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 16 publications
(19 reference statements)
2
37
0
Order By: Relevance
“…Across different sub-fields of psychology, a diverse set of dual-process models have been proposed, including analytic vs. heuristic (Kahneman, 2011, Evans, 2008, Evans and Stanovich, 2013, Evans, 2003), conscious vs. unconscious (Dijksterhuis et al., 2006, Lassiter et al., 2009), associative versus rule based (Ashby & O'Brien, 2005), goal-directed vs. habitual (Dickinson, 1985), cognitive vs. affective (Bechara et al., 1997), and reflective (C-system) vs. reflexive (X-system) models (Lieberman, 2007). Recently, there have been discussions about how stress modulates leaning and decision making through the lens of duality models.…”
Section: A Stress Induced Deliberation-to-intuition (Sidi) Modelmentioning
confidence: 99%
“…Across different sub-fields of psychology, a diverse set of dual-process models have been proposed, including analytic vs. heuristic (Kahneman, 2011, Evans, 2008, Evans and Stanovich, 2013, Evans, 2003), conscious vs. unconscious (Dijksterhuis et al., 2006, Lassiter et al., 2009), associative versus rule based (Ashby & O'Brien, 2005), goal-directed vs. habitual (Dickinson, 1985), cognitive vs. affective (Bechara et al., 1997), and reflective (C-system) vs. reflexive (X-system) models (Lieberman, 2007). Recently, there have been discussions about how stress modulates leaning and decision making through the lens of duality models.…”
Section: A Stress Induced Deliberation-to-intuition (Sidi) Modelmentioning
confidence: 99%
“…This series of experiments is being met by a burst of experimental critiquese.g., Lassiter et al, 2009;Rey et al, 2009;Waroquier et al, 2009. In essence, these experiments consist of failures to replicate and the identification of experimental biases.…”
Section: Unconscious Thinking-decision?mentioning
confidence: 96%
“…Lassiter et al . (2009[49]), for example, concluded that “Such judgments are ultimately a product of conscious rather than unconscious thought” (p. 361).In Newell & Shanks (in press[53]), there is a detailed and important set of methodological critiques of research purporting to find “unconscious influences on decision-making” in three paradigms usually labelled multiple cue judgement, deliberation-without-attention, and decision under uncertainty. The authors find a tendency to accept unconscious influences despite inadequate assessment of awareness and various ignored artefacts.…”
Section: What Consciousness Explains?mentioning
confidence: 99%
“…Lassiter et al . (2009[49]), for example, concluded that “Such judgments are ultimately a product of conscious rather than unconscious thought” (p. 361).…”
Section: What Consciousness Explains?mentioning
confidence: 99%